Nazism, the Holocaust, and the Middle East : Arab and Turkish responses - Nicosia, Francis R. 1944- HerausgeberIn; Ergene, Boğaç A. 1971- HerausgeberIn; Responses in the Middle East to National Socialism and the Holocaust, 1933-1945 (Vermont studies on Nazi Germany and the Holocaust, 2018)
Given their geographical separation from Europe, ethno-religious and cultural diversity, and subordinate status within the Nazi racial hierarchy, Middle Eastern societies were both hospitable as well as hostile to National Socialist ideology during the 1930s and 1940s. By focusing on Arab and Turkish reactions to German anti-Semitism and the persecution and mass-murder of European Jews during this period, this expansive collection surveys the institutional and popular reception of Nazism in the Middle East and North Africa. It provides nuanced and scholarly yet accessible case studies of the ways in which nationalism, Islam, anti-Semitism, and colonialism intertwined, all while sensitive to the region's political, cultural, and religious complexities